(untitled) (Research, Society and Development, 2022)
Research on the clinical use of Lasers began in the 1960s and from the 1990s onwards, clinical studieswere intensified. The use of light-based technologies, Lasers and LEDs, has increased exponentially, with excellent clinical results and patient satisfaction. Despite the great expansion of clinical use, the evolution of teaching in dental schools shows signs of not following the same pace and the knowledge necessary for the safe use of Lasers and LEDs is not taught in other subjects of the dentistry course. Thus, the objective of this study was to verify the level of knowledge about Lasers and LEDs among dentistry students from a school that offers the subject of Laser in dentistry in na elective way in its curricular structure. For that, a structured questionnaire was applied to first year and last year dental students. Ninety-nine students consented to participate in the research and answered the questionnaire. The results were able to demonstrate that the knowledge level about Lasersand LEDs among dentistry students has been increasing and a specific discipline in the area, even if optional, contributes to add a significant level of knowledge and confidence to dentistry students.